Developing Individual Multilingualism in Higher Education: Prospects and Dilemmas - Cybulska, Katarzyna (Verbum, 2011)
In the light of the European language policy, higher education institutions are assigned an enormous role and expectations when it comes to promoting individual multilingualism (i.e. plurilingualism). Drawing upon the language policy developments and research in this area, this paper aims to show the pathways to developing learners’ plurilingual/multilingual repertoires at the tertiary level. Accordingly, the author will outline the psycholinguistic tenets of individual multilingualism as well as current priorities and recent tendencies in what has been referred to as plurilingual education. Such concepts as partial and transversal competences, intercomprehension, learning L3 through L2, CLIL, interdisciplinary communicative competence and international cooperation will be highlighted. The emphasis will be placed on the design and implementation of a coherent language policy by higher education institutions; in addition, a number of good practices institutions may take pride in and the obstacles they ultimately face will be described.